Ragion di stato e salvezza dell'anima Il riscatto dei cristiani captivi in Maghreb attraverso le redenzioni mercedarie (1575-1725) - BOSCO, MICHELE (Premio Ricerca «Città di Firenze», 2018)
During the Modern Age centuries, thousands of individuals were captured by pirates in the Mediterranean Sea and were enslaved in the land of the 'unfaithful: after being taken as prisoners, they were sold, forced to hard labour and rowing in the galleys or destined for redemption. Institutions, city judges and religious orders were involved in the redemption of Christians in the land of Islam, including the Mercedarians. This book reconstructs the history and activity of this Order and other protagonists of that activity in Italy and the Iberian Peninsula. After studying the books of redemption accounts sent to North Africa between the late 16th century and the early 18th century, the author shows how even religious men followed the orders of political power, and how that charitable activity ended up surrendering to economic and national interests.